Transmission of Monetary Policy and Bank Heterogeneity in Colombia (2018)
This study provides evidence of bank heterogeneity in Colombiafor the period 2002-2014 and analyzes how bank-specific character-istics determine the bank-lending channel for monetary policy. Toanalyze bank heterogeneity, this study estimates technical (cost) effi-ciency using Stochastic Frontier Analysis, which also allows for themeasurement of Returns to Scale and a Lerner Index to proxy mar-ket power in the loans market. This study also provides measuresof capitalization, liquidity, and the commonly used ratios of financialand operational efficiency with bank’s balance-sheet data. Further-more, using a long and unbalanced panel, this study finds evidence ofthe existence of a bank-lending channel and finds that this transmis-sion mechanism is determined by bank-specific characteristics. Theresults suggest higher technical and operational efficiency, capitaliza-tion, liquidity and market power, increase the sensitivity of loans dis-bursements to monetary policy shocks, while higher returns to scalelowers this sensitivity.